Growth and Production of Long Bean Plants (Vigna sinensis L.) on Concentration Level of Liquid Organic Fertilizer Banana Webs and Chitosan - Zahanis Zahanis; Fatimah Fatimah; Yulia Anggraini (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
The aim of this study was to determine the interaction of the concentration of liquid organic fertilizer on banana weevil and chitosan on the growth and yield of long beans. This study used a completely randomized design, with 2 factors. The first factor is banana weevil liquid organic fertilizer consisting of 3 levels, namely, 0 ml/L, 45 ml/L, and 90 ml/L. The second factor was chitosan consisting of 3 levels, namely, 0 ml/L, 3 ml/L, and 6 ml/L. Based on the experimental results, it can be concluded that there is an interaction between liquid organic fertilizer of banana weevil and chitosan with the parameters of plant length and number of branches. Increasing the concentration of liquid organic fertilizer on banana weevil can increase the number of pods and the weight of fresh pods per plant, the highest fresh pod weight per plant is 1.20 kg/plant with a concentration of 90 ml/L. The administration of chitosan concentration only affected the number of pods parameter, the highest number of pods was in the provision of 6 ml/L, namely 55.55 pods/ plant.